The Arab Uprising: Indicators of Female Health, Development and Empowerment - Deonandan, Raywat; Stanley, Charmaine; El-Hindi, Tania (Université d'Ottawa | University of Ottawa, 2012)
Objectives: Our objective was to explore whether traditional measurements of female empowerment used in population health and development studies could detect a role played by women in the 2011 Arab Spring revolutions. Methods: Twenty-one state-level indicators of health, development and female empowerment were extracted fROm public databases maintained by the World Bank, UNDP and CIA World Factbook and compared between the six so-called Arab Spring nations, as well as eleven Middle Eastern nations deemed to be at risk for revolution. Results: Population sex ratio parity and the percentage of women completing primary education was significantly greater (p<0.05) in nations having successfully revolted, compared to all other examined Arab nations. Conclusions: The extent to which education and sex ratio parity are truly predictive of social engagement and change need to be more deeply investigated. While traditional health and development indicators ostensibly showing female social, legal and economic engagement failed to show an association between women’s empowerment and Arab Spring revolution, given the documented role of women in the Egyptian uprising, this may be an indication of the insufficiency of existing indicators to detect the subtle and multifactorial role of women in dramatic political change.
Keywords: gender; indicators; middle east; arab; womens health